PROPUESTA ORGANIZATIVA Y DE PLANIFICACIÓN DE MARKETING PARA LA EMPRESA PRODUCTOS ZOILITA DE LA CIUDAD DE GONZANAMÁ, DE LA PROVINCIA DE LOJA - Betancourt Bravo, Jorge Luis (2015)
In the present investigation has been raised as a general goal the development of this paper entitled "ORGANIZATIONAL PROPOSAL AND PLANNING MARKETING COMPANY PRODUCTS ZOILITA CITY Gonzanamá, PROVINCE OF LOJA", it will bring valuable knowledge Company Products for Zoilita. In paragraph (e) of materials and methods other methods of the inductive method was used were determined, allowed to establish the reality found in the company Products Zoilita from the particular to the general, the statistical method, it facilitated tabulating surveys applied to families of now Goods Zoilita and workers and manager of the company; within the techniques allowed to apply a survey of families in the province of Loja, employees and an interview with the manager of the company, under these conditions the data helped to formulate the strengths, weaknesses, opportunities and threats, always supporting research field, the design of the SWOT matrix. In paragraph (f) of the external analysis results they were conducted in the box Matrix assessment of external factors, once the weighting assigned to each of the external factors that influence the company Products Zoilita, the result was obtained 2.60 weighted. The results are added. The total weighted value can not exceed 4. The weighted average value is 2.60. A total weighted value May to 2.5 indicates that the company responds well to the opportunities and threats, while a weighted value less than 2.5 indicates that you are not taking advantage of opportunities and threats that can do great 5 damage. The weighted total is 2.60, indicating that the company is taking advantage of some opportunities and threats that may harm if not potentiate opportunities. According to the result of the Evaluation Matrix internal factors of the company products Zoilita, determined as weighted result of 2.68; It means that the company exists a predominance of strengths of weaknesses; therefore company has no internal problems that may interfere with the growth of the same and also has a normal development in the local market. In paragraph (g) Discussion by Matrix High Impact, four objectives, among which are raised; 1. Using social networks to improve communication and information with customers; 2. Perform an advertising plan to publicize the company's products "Zoilita products" on the market. 3. Implement a plan to increase sales promotions. 4. Attract new markets by offering low prices on their products; All these objectives have a total budget of $ $ 11372.00 for compliance. Finally in subparagraphs (h) and (i) has come to determine the conclusions and recommendations based on market research and the proposed recommendations should be made against the implementation of the Organizational Plan and Planning Marketing Company Products Zoilita Gonzanamá city of the province of Loja. And finally I present the recommendations pose with such affection to this Family Business Products Zoilita, to welcome them and to contribute and collaborate with economic development.